Growing the Youth Olympic Games: Comparing millennial generation sport festival engagement - Judge, L. W.; Petersen, J. C.; Bellar, D. M.; Lower, L. M.; Schoeff, M. A.; Blake, A. S.; Zupin, D.; Nordmann, N. (International Journal of Exercise Science, 2021)
Despite the continued growth of the Olympic Games (OG), the Youth Olympic Games (YOG) has received minimal attention from mainstream media since its introduction in 2010. The purpose of this study was to examine and compare event awareness and consumption intention for the 2012 Winter YOG to two international sport events occurring in the same year. A survey instrument was utilized to examine and compare event awareness, consumption intention, and logo identification for three international sport events within a millennial generation sample. The study showed significant differences in personal and public awareness between the three sport events, with personal (r = .313, p = .001) and public (r = .331, p = .001) awareness for the YOG demonstrating a positive correlation with consumption intention. This study is an important assessment of the YOG event awareness that can be utilized by the International Olympic Committee (IOC) to better understand and engage their participants and audience. Successful promotion of the YOG may require a transformation of the current marketing strategies that are utilized. The YOG has great opportunity for success in the global sport market to leave behind the status of the best kept secret in sport.